Combinations of Lemongrass and Star Anise Essential Oils and Their Main Constituent: Synergistic Housefly Repellency and Safety against Non-Target Organisms - Mayura Soonwera; Jirisuda Sinthusiri; Hataichanok Passara; Tanapoom Moungthipmalai; Cheepchanok Puwanard; Sirawut Sittichok; Kouhei Murata (My University, 2024)
The present study evaluated the housefly repellency of single-component formulations and combinations of lemongrass and star anise essential oils (EOs) and their main constituents. The efficacies of the combinations were compared against those of single-component formulations and DEET. Safety bioassays of all formulations and DEET on non-target species—guppy, molly, dwarf honeybee, and stingless bee—were conducted. GC–MS analysis showed that the main constituent of lemongrass EO was geranial (46.83%) and that of star anise EO was trans-anethole (92.88%). All combinations were highly synergistic compared to single-component formulations, with an increased repellent value (IR) of 34.6 to 51.2%. The greatest synergistic effect was achieved by 1.0% lemongrass EO + 1.0% trans-anethole combination, with an IR of 51.2%. The strongest, 100% repellent rate at 6 h was achieved by 1.0% geranial + 1.0% trans-anethole. They were twice as effective as DEET and caused obvious damage to housefly antennae under microscopic observation. All single-component formulations and combinations were benign to the four tested non-target species. In contrast, DEET was highly toxic to them. The synergistic repellency and biosafety of these two combinations are compellingly strong support for developing them into an effective green repellent.
Keywords: Anethole; DEET; Housefly; Guppy; Insect Pest Control Strategies